Lattice spacing changes accompanying isometric tension development in intact single muscle fibers. - Bagni, M A (1994)
The myosin lattice spacing of single intact muscle fibers of the frog, Rana temporaria, was studied in Ringer's solution (standard osmolarity 230 mOsm) and hyper- and hypotonic salines (1.4 and 0.8 times standard osmolarity respectively) in the relaxed state, during "fixed end" tetani, and during shortening, using synchrotron radiation. At standard tonicity, a tetanus was associated with an initial brief lattice expansion (and a small amount of sarcomere shortening), followed by a slow compression (unaccompanied by sarcomere length changes). In hypertonic saline (myosin lattice compressed by 8.1%), these spacing changes were suppressed, in hypotonic saline (lattice spacing increased by 7.5%), they were enhanced. During unloaded shortening of activated fibers, a rapid lattice expansion occurred at all tonicities, but became larger as tonicity was reduced. This expansion was caused in part by the change in length of the preparation, but also by a recoil of a stressed radial compliance associated with axial force. The lattice spacing during unloaded shortening was equal to or occasionally greater than predicted for a relaxed fiber at that sarcomere length, indicating that the lattice compression associated with activation is rapidly reversed upon loss of axial force. Lattice recompression occurred upon termination of shortening under standard and hypotonic conditions, but was almost absent under hypertonic conditions. These observations indicate that axial cross-bridge tension is associated with a compressive radial force in intact muscle fibers at full overlap; however, this radial force exhibits a much greater sensitivity to lattice spacing than does the axial force.